Evaluating the time limit at maximum aerobic speed in elite swimmers. Training implications - Renoux, J. C. (Archives of Physiology and Biochemistry, 2001)
The aim of the present study was to make use of the concepts of maximum aerobic speed (MAS) and time limit (tlim) in order to determine the relationship between these two elements, and this in an attempt to significantly improve both speed and swimming performance during a training season. To this same end, an intermittent training model was used, which was adapted to the value obtained for the time limit at maximum aerobic speed. During a 12 week training period, the maximum aerobic speed for a group of 9 top-ranking varsity swimmers was measured on two occasions, as was the tlim. The values generated indicated that: 1) there was an inverse relationship between MAS and the time this speed could be maintained, thus confirming the studies by Billat et al. (1994b); 2) a significant increase in MAS occurred over the 12 week period, although no such evolution was seen for the tlim; 3) there was an improvement in results; 4) the time limit could be used in designing a training program based on intermittent exercises. In addition, results of the present study should allow swimming coaches to draw up individualized training programs for a given swimmer by taking into consideration maximum aerobic speed, time limit and propelling efficiency.